Implementasi Kebijakan Merit Sistem Dalam Promosi di Badan Kepegawaian Pendidikan Dan Pelatihan Kota Gorontalo - Gani, Nandar Alfian; Tjokra, Muhamad Reza; Tabo, Sarfan; Nuna, Muten S (Universitas Muara Bungo, 2025)
The purpose of this study was to determine the implementation of the Merit System policy in the employee promotion process at the Gorontalo City Education and Training Personnel Agency (BKPP), especially in terms of planning, implementation, and assessment aspects. The Merit System is a personnel management principle based on employee qualifications, competencies, and performance, so that it is expected to produce objective and fair promotions. This study was conducted at the Gorontalo City BKPP Office located on Jalan 23 Januari, Biawao Village, South City District, Gorontalo City, Gorontalo Province. Data collection techniques used included observation, in-depth interviews with related officials and stakeholders, and documentation studies of employee promotion policies and procedures. Data were analyzed using a qualitative approach to obtain an in-depth picture of the implementation of the policy. The results of the study indicate that the implementation of the promotion policy in the Gorontalo City BKPP environment has not fully referred to the Merit System principle. Based on the theory of policy implementation by George C. Edward III which includes variables of communication, resources, disposition, and bureaucratic structure, it was found that there were a number of obstacles. One of the main weaknesses is the lack of a Job Competency Standard (SKJ) that should be a reference for promotions. In addition, the absence of an assessment process in assessing employee competency is an obstacle to implementing objective and transparent promotions. This shows the need for improvement in promotion policies to be in line with the principle of meritocracy.